The king's evil [large type] - Taylor, Andrew, 1951 October 14- (Taylor, Andrew, 1951 October 14- James Marwood and Cat Lovett series., 2020)
"In the tradition of "Dr. Jekyll and Mr. Hyde" and, more recently, Bernhard Schlink's "The Reader," comes a provocative and unsettling modern morality tale of subtly evolving horror--a mesmerizing debut from a brilliant young writer"--